Premature rupture of membranes and its association with neonatal pneumonia in pregnant women attended in a tertiary Hospital in Lima, Peru - Juárez-Peralta, Máryori (2020)
Objective: To determine the association between premature rupture of membranes and pneumonia in newborns in a tertiary hospital in Lima, Peru.  Materials and methods: Retrospective cohort study, the selection of the sample was simple random probability without replacement, the sample calculated to raise comparable and balanced groups was obtained. The sample size resulted in 102 pregnant women out of 102 pregnant women, 51 with ruptured membranes and 51 without this pathology, in the María Auxiliadora hospital between 2016 and 2017, the association of PMR and neonatal pneumonia was determined. The SPSS v.17 program was used for a descriptive analysis and frequency tables using a relative risk with their respective 95% confidence intervals. Results: In total, of the 102 pregnant women in the sample and their respective products, 45% had pneumonia and 55% had no pneumonia. According to the analysis, the frequency of neonatal pneumonia was higher in the products of those pregnant women who had RPM (58.8%), compared to those who did not have RPM (31.4%) (p <0.00; RR: 2,340, 95% CI: 1,528 - 10,759) demonstrated significant association to RPM. Pathological laboratory and radiological examinations also demonstrated a significant association. Conclusions: The RPM is significantly associated with neonatal pneumonia, with a 3-fold increased risk in products from pregnant women with RPM compared to those who did not have RPM.